The social context for value co-creations in an entrepreneurial network: Influence of interpersonal attraction, relational norms and partner trustworthiness. Issue 2 (11th April 2016) - Ferguson, Ronald; Schattke, Kaspar; Paulin, Michele
Abstract : Purpose: – The purpose of this paper is to study micro-level research into the social dimensions of entrepreneurial partnerships assessed by the influences of: the degree of interpersonal attraction, the strength of relational norms and the level of partner trustworthiness on value co-creations in an emerging biotechnology network. Design/methodology/approach: – Financial and scientific partnerships were investigated by structured interviews with entrepreneurs. Financial partnerships were also studied using interviews with lead investors. Research design and analyses were based on a Conditional Process Model. Findings: – Partner trustworthiness was found to be critical for the co-creation of value in both types of partnerships. In financial partnerships, the level of interpersonal attraction and relational norms strength acted independently as antecedents of partner trustworthiness. Only the entrepreneur linked interpersonal attraction directly to value co-creation. Both entrepreneurs and lead investors perceived the association between interpersonal attraction and co-created value to be mediated through partner trustworthiness. Only the lead investor perceived this mediation to be moderated by relational norms strength. However, in scientific partnerships, relational norms strength, but not interpersonal attraction, contributed to partner trustworthiness that subsequently effected value co-creation. The entrepreneur's trustworthiness perception in both types of partnerships was mainly due to a partner's reputation, whereas for lead investors it was primarily the perceived reliability of the entrepreneur. Originality/value: – This research points out the challenges of measurement and interpretation of network research. Theoretical conclusions based on only one partner's perspective and in one context would not be sufficient to describe the complexity of value co-creations in entrepreneurial networks. Also, the cooperative social, rather than competitive opportunistic nature of entrepreneurial knowledge-intensive networks was confirmed.